ANALISIS KESULITAN MENYELESAIKAN MASALAH MATEMATIS BERKAITAN DENGAN PERTANIAN DITINJAU DARI MOTIVASI BELAJAR MATEMATIS MAHASISWA - Ali, Ferdinandus Ardian; Payong, Polikarpus; Jandu, Inosensius H.; Fausta, Kurniati P. (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2023)
This study aims to find out the difficulties of students in solving mathematical problems related to agriculture in terms of mathematical learning motivation. This study uses qualitative methods, and the main instrument is the researcher himself, while the supporting instruments are questionnaires, tests and interviews. Data collection uses a triangulation process, and data analysis adapts the Milles and Huberman analysis model. The research subjects selected were 1 student who had low mathematical learning motivation (MBMR subject), 1 student who had moderate mathematical learning motivation (MBMS subject), and 1 student who had high mathematical learning motivation (MBMT subject). The results showed that in the step of understanding the problem, the three subjects did not experience any difficulties. In the step of making a problem-solving plan, the three subjects also used the graphical method and both did not experience difficulties. While in the step of carrying out problem solving, each subject finds their own difficulties that are different from each other.